Anger Management To Reduce Angry Behavior In Schizophrenia Patients - Azhar, Ryan Ainul; Pratikto, Herlan (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Schizophrenia is a serious mental disorder characterized by hallucinations, delusions, disorganized thoughts, and difficulty managing emotions, often leading to aggressive behavior.This study explores the effectiveness of anger management interventions in helping patients with schizophrenia manage aggression, specifically targeting a 38-year-old patient diagnosed with paranoid schizophrenia. The study employs a qualitative approach through observations, interviews, and psychological testing to assess the patient's psychological state and identify factors contributing to emotional dysregulation. Psychological assessments, including WAIS, SSCT, WWQ, SRQ-20, and projective tests, revealed that the patient displayed a below-average IQ, social withdrawal, mood instability, impulsivity, and paranoia. The intervention included six sessions of anger management techniques based on Novaco’s cognitive-behavioral approach, aiming to help the patient recognize anger triggers, improve emotion regulation, and foster positive coping strategies. Results demonstrated a notable reduction in aggressive behaviors, with the patient showing progress in emotional control, appropriate social communication, and engaging in beneficial activities to redirect anger. Although some behavioral challenges persisted, the patient exhibited improved self-awareness and applied relaxation techniques learned during the intervention. This study highlights the significance of individualized anger management programs as an effective approach for reducing aggression in schizophrenia patients.